Optimization Methods for the Partner Units Problem - Aschinger, M; Drescher, C; Friedrich, G; Gottlob, G; Jeavons, P; Ryabokon, A; Thorstensen, E (Berlin‚ Germany, 2011)
In this work we present the Partner Units Problem as a novel challenge for optimization methods. It captures a certain type of configuration problem that frequently occurs in industry. Unfortunately, it can be shown that in the most general case an optimization version of the problem is intractable. We present and evaluate encodings of the problem in the frameworks of answer set programming, propositional satisfiability testing, constraint solving, and integer programming. We also show how to adapt these encodings to a class of problem instances that we have recently shown to be tractable.